Naturalisme og kristendom: Et dogmatisk perspektiv - Teglbjærg Kristensen, Johanne Stubbe (Dansk Teologisk Tidsskrift, 2014)
Against the temptation to seek a complete conceptual clarification of the relationship between Naturalism and Christianity, this article argues from a dogmatic perspective that the relationship between Naturalism and Christianity demands an approach that takes into consideration the limits and complications of dogmatic conceptuality itself. This approach proceeds from the post-dialectical awareness of a highly dialectical relationship of the concepts of Naturalism and Christianity, which makes them impossible to synthesize dogmatically and yet, equally impossible to conceive of as irreconcilable. By moving from the post-dialectical understanding of Naturalism in relation to the notion of theology, revelation and faith to the history and appearance of the concept of Naturalism in its relation to Supernaturalism, it is argued that Naturalism and Christianity shares an ambiguous notion of human rationality, which according to post-dialectical theology is due to a deeper complication of subjectivity; this puts certain methodological demands on a theology of Naturalism.